HUBUNGAN JENIS KELAMIN TERHADAP MOTIVASI REMAJA DALAM MELAKSANAKAN PERILAKU CUCI TANGAN PAKAI SABUN DI MASA COVID - 19 - Nurma Zela Gustina; Widyatuti; Wiwin Wiarsih (Journal Of Nursing Science Research, 2025)
Confirmed cases of COVID-19 in the adolescent are unavoidable. There needs to be motivation from adolescent to carry out 3M behavior as an effort to prevent the transmission of COVID-19, especially in the adolescent. Health behavior can be influenced by gender, because in adolescence lend to be active in peer groups of the same gender. So it is important to know the relationship between gender and adolescent behavior in implementing 3M behavior during the COVID-19 pandemic. Aim of this study was to determine the relationship between gender and adolescent motivation in carrying out 3M behavior during the COVID-19 pandemic. This research method was carried out with descriptive correlative design on 427 adolescents in the city of Palembang. The results of statistic test analysis showed that there was a significant relationship between gender and adolescent motivation in implementing 3M behavior during the COVID-19 pandemic with a p value of 0.001 (p < 0.05). These results show that statistically there is a significant difference in motivation scores between male and female adolescents in carrying out 3M behavior during the COVID-19 pandemic. The conclusion is that knowing gender is related to adolescent motivation in implementing 3M behavior, so to increase the effectiveness of the results of health promotion, it is recommended to create a gender-based health promotion program in the aggregate of adolescents.